Effect of Powdered Commercial and Activated Charcoal on Removal of Copper and Nickel from Wastewater of Electroplating Industry - Tandel, M.A.; Oza, B.N. (Asian Journal of Chemistry, 2016)
Batch adsorption kinetic studies were carried out on electroplating wastewater with powdered commercial charcoal (specific surface area 5401.69 cm2/g) and powdered activated charcoal (specific surface area 5802.35 cm2/g) as absorbents. The effect of concentration of adsorbent and contact duration were studied on copper and nickel removal efficiency. Higher efficiency (x/m value) of adsorption is obtained at lower dose of powdered activated charcoal (PAC), which removes 61.28% copper and 50.35% nickel at a maximum dose of 25 g/L, whereas similar dose of powdered commercial charcoal (PCC) removes 28.74% copper and 24.80% nickel respectively. From the results it can be concluded that PAC may be most effective than PCC in the removal of copper and nickel at very low dose. Their efficiencies are moderately affected by the pH and COD of the wastewater.